EDUKASI DALAM UPAYA MENCEGAH STUNTING BAGI MASYARAKAT DUSUN KAJEN DESA SAMBIREJO NGAWI MENGGUNAKAN AKSI ABCDE - Sawitri, Satwika Budi; Suciati, Anugerah; Fatikha, Asa Wafda; Putri, Cendikia; Safitri, Gayuh Aulia; Sofia, Lutfa Selfi; Almas, Natarina Citra; Salimah, Safna Hanif (Jurnal Abdimas Kesehatan (JAKes), 2025)
Insufficient nutritional intake can cause stunted growth in children. This growth disorder is called stunting. Stunting is a condition of growth failure in toddlers (infants under five years old) due to chronic malnutrition so that the child is too short for his age. Stunting has an impact on the quality of human resources (HR), which ultimately will reduce HR productivity and the demographic bonus (a large increase in the number of productive population) is not utilized properly. The purpose of this community service is to increase the knowledge of mothers in Kajen hamlet, Sambirejo village, Ngawi Regency with toddlers by providing education. Education is provided by presenting material using direct presentation methods and questions and answers regarding the signs, symptoms or occurrences of stunting in children. The method used in this community service activity is the provision of information and education followed by a pre-test and post-test. The results of the activity show that there is an increase in the level of knowledge of mothers in Kajen hamlet. The level of enthusiasm of mothers in providing information also shows a real impact that awareness of events for children is very necessary to be aware of. The conclusion of this community service activity is that by increasing the knowledge of mothers with toddlers and young children, it is hoped that it will have an impact on mothers and parents to overcome and prevent stunting in children.